Peran Kepemimpinan Wali Nagari Perempuan dalam Mewujudkan Sustainable Development Goals (SDGs) Desa di Kabupaten Pesisir Selatan - Fitri, Annisa; Rinawati, Rinawati; Khudri, Nur Saadah; Saputra, Nika; Baguno, Rainal (Faculty of Social Science, Universitas Negeri Padang, 2023)
This research was conducted to understand the role of female Nagari Guardians in realizing Sustainable Development Goals (SDGs) in two Nagari in Pesisir Selatan Regency, although since 2007 there has been a law that allows women to become village heads. However, in reality there are still very few women who lead nagari in Minangkabau, as evidenced by the 182 nagari in Pesisir Selatan Regency, there are only 2 female Nagari Wali. The research methodology used was qualitative using in-depth interview techniques, observation and document analysis. The results of the research showed that female Nagari Wali applied situational leadership, adjusting their leadership style and actions based on the situation. Their role in realizing the SDGs includes decision making, village development planning, village data collection to prioritize national programs, and adapting to new habits through the